E Zakat Education In Islamic Boarding Schools: The Relationship Between Persuasive Communication By The Darussyifa Islamic Boarding School Upz And Increasing Interest In Zakat - YASPIDA, YUSUP (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Zakat education in Islamic boarding schools is an important instrument in fostering religious awareness and reducing social inequality through the fair distribution of wealth. However, the potential of zakat in Indonesia is still far from being realized, including in Islamic boarding schools, which have a large Muslim community base. This study aims to analyze the role of zakat education through the persuasive communication strategies of the Zakat Collection Unit (UPZ) of the Darussyifa Al-Fithroh YASPIDA Islamic Boarding School in Sukabumi in increasing the interest of muzaki. The research method used a quantitative approach with a field study design. The research sample consisted of 63 respondents determined using the Slovin formula from a population of 168 muzaki. Data were collected through a five-point Likert scale questionnaire and then analyzed using significance tests and determination coefficients. The results showed that the motivation dimension had a significant effect on the interest of muzaki in paying zakat (p = 0.004), while the communicator's ability dimension was not significant (p = 0.127). The R² value of 0.931 indicates that the persuasive communication model can explain 93.1% of the variation in muzaki interest. However, the message relevance (45.1%) and follow-up motivation (50.7%) indicators are still relatively low. These findings confirm that emotional factors are more dominant than technical skills in influencing muzaki interest. The practical implications of this study encourage the optimization of peripheral pathways in the Elaboration Likelihood Model through emotional narratives, inspirational figures, and mustahik testimonials. Further research is recommended to explore the role of digital media, audience segmentation, and visual storytelling in strengthening the message of zakat.